Modeling Support Loss in Torsional Mode Vibrations of a Micromechanical Disk Resonator with Two L-Shaped Support Beams - Bagheri, M.; Bijari, A.; Imanparast, M.; Raghebi, M. (Engineering, Technology & Applied Science Research, 2017)
In this paper, a new micromechanical disc resonator with two L-shaped horizontal support beams in torsional mode vibrations has been proposed. The proposed micromechanical resonator has been studied in the field of natural frequencies and support loss. In order to verify the findings of natural frequencies, the analytical results are compared to the simulation results given by ANSYS software. A good agreement between analytical and simulation results is shown. In addition a closed-form equation for support loss quality factor in torsional mode vibrations of the proposed micromechanical resonator is presented. The results show that using L-shaped support beams can improve the support loss quality factor up to two times.